Uwagi o cywilizacji stosowania przepisów prawa administracyjnego - Adamiak, Barbara (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
The application of administrative law, as well as the application of civil law combine the common values on which the entire legal order is based, the values resulting primarily from constitutional principles. The whole legal order is based on unity, which means that when interpreting the provisions of substantive administrative law, one can not derive the one that would deny this legal order, including undermining or excluding the protection of values adopted in civil law, eg property rights. Administrative law permeates common values with values adopted in civil law, whereby the authority of public administration is obliged to defend these values, including interpretation of regulations and determination of the actual state in a given case.
Keywords: the burden of proof; transfer of the value of civil law to the ground of administrative law; the value of civil law; socio-economic effects; the principle of social coexistence